Menguji Dampak Omicron terhadap Harga Saham dan Volume Transaksi: Studi Kasus pada Indeks Saham LQ-45 di Bursa Efek Indonesia - Adiputra, Andre Kussuma; Meilaretasya, Nabilla Eka; Rohmah, Khaula Lutfiati (RJABM (Research Journal of Accounting and Business Management), 2024)
Rapid stock price movements, especially during the ongoing pandemic, demand heightened attention from investors. The unpredictability of stock prices and market reactions to COVID-19 and its variants poses a challenge in predicting their future trends. Beyond stock prices, examining the trading volume of listed companies is crucial. This research aims to analyze potential differences in stock prices and transaction volumes within the LQ-45 Stock Index following the Omicron announcement in Indonesia. The study focuses on the 14 days preceding and following the Omicron announcement, utilizing a saturated sampling approach. The data is analyzed through the Wilcoxon Signed Rank Test for hypothesis testing. Findings suggest significant disparities in stock prices and transaction volumes before and after the Omicron announcement. The research concludes that news or announcements related to the Omicron variant adversely impact the capital market, aligning with event study principles. Such announcements influence market responses, resulting in fluctuations in stock prices and transaction volumes.